1999
DOI: 10.1111/j.1600-0447.1999.tb10693.x
|View full text |Cite
|
Sign up to set email alerts
|

How are mental disorders seen and where is help sought in a rural Ethiopian community? A key informant study in Butajira, Ethiopia

Abstract: One hundred key informants were interviewed about their awareness, attitudes and practices regarding mental illness using the Key Informant Questionnaire developed by WHO. Case vignettes of seven common neuropsychiatric disorders were presented to the key informants. Tnformants' awareness about these disorders and help‐seeking practices for mental and physical symptoms or conditions were assessed. An additional question on the prototype symptoms of mental disorders was also posed. Among the presented seven con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
97
2
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(114 citation statements)
references
References 13 publications
13
97
2
2
Order By: Relevance
“…1 The high prevalence of negative attitudes towards epilepsy has been highlighted by several studies, carried out in diverse communities including India, Ethiopia, Hong Kong and the United States. [11][12][13][14] However, a higher level of education correlates positively with awareness, knowledge and attitude concerning epilepsy. Community-based studies have reported that better-educated individuals offer more favorable opinions and display positive attitude (Mirnics et al, Chung; Hills and Mackenzie; Jensen and Dam).…”
Section: Introductionmentioning
confidence: 99%
“…1 The high prevalence of negative attitudes towards epilepsy has been highlighted by several studies, carried out in diverse communities including India, Ethiopia, Hong Kong and the United States. [11][12][13][14] However, a higher level of education correlates positively with awareness, knowledge and attitude concerning epilepsy. Community-based studies have reported that better-educated individuals offer more favorable opinions and display positive attitude (Mirnics et al, Chung; Hills and Mackenzie; Jensen and Dam).…”
Section: Introductionmentioning
confidence: 99%
“…In line with this, more recent research provides evidence of a more fluid and nuanced understanding of culture. 1,[13][14][15][16][17] Although there is little data investigating explanatory models of traditional healers in South Africa, a Zimbabwean study involving traditional healers (as well as other community members) found that respondents were readily able to identify mentally ill patients based on their behaviours (e.g. wandering away from home; eating or smearing feces; laughing at inappropriate times; impaired self-care such as not washing; and eating dirty food).…”
Section: Introductionmentioning
confidence: 99%
“…Dohrenwend & Dohrenwend 1974;Hoenig & Wijestinghe 1979;Gaw 1993;Triandis 1996;Castillo 1997;Kirmayer et al 1997;Banerjee 1998;Battistone et al 1998;Alem et al 1999;Lopez & Guarnaccia 2000;James & Prilleltensky 2002). Most research commenting on the in¯uence of culture to shape knowledge and beliefs of psychopathology has been directed toward identifying cultural differences in theories of illness causation (Murdock 1980;Fabrega 1989;Lewis-Ferandez & Kleinman 1994), whether diagnostic categories of illness are recognised in different cultures (Jilek 1982;Fabrega 1992Fabrega , 1993Rogler 1993;Draguns 1995;Weiss et al 1995), if cultural variations in the stigmatisation of the mentally ill exist (Murphy 1976;Cole et al 1995;Raguram et al 1996;Carter & Neufeld 1998;Littlewood 1998), and whether over-representation in psychiatric morbidity indices of, in particular, migrating ethnic minorities can be explained through preferences for alternative cultural-based treatments (Kleinman 1980;Helman 1990;Littlewood 1992;McKenzie 1999;Sharpley et al 2001).…”
Section: Introductionmentioning
confidence: 99%